PREDICTION OF THE DIAMOND POTENTIAL OF TRIASSIC ROCKS IN TAIMYR - Grakhanov S.A.; Yadrenkin A.V. (My University, 2007)
The diamond potential of Taimyr was first predicted by V.S. Sobolev and G.G. Moor after study of samples of micaceous kimberlites discovered by N.N. Urvantsev in 1929. Alkaline basic rocks, similar to the kimberlite-associated melilitic basalts of South Africa, were discovered in Taimyr by Sobolev [1] and Moor (based on consultations with Sobolev) [14]. Sobolev made recommendations pertaining to the prospecting for kimberlites and diamonds in a special report submitted to Classified Report Funds of the Karpinskii All-Russia Research Institute of Geology, St. Petersburg in 1941 (inventory no. 1773).
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая